On the Legacy of the Land: Ideology Criticism of Walter Brueggemann and John Steinbeck - Kočí, Kateřina (Theology today, 2021)
This article addresses the sensitive, religious-political issue of the promised land. It discusses this issue from the perspective of the criticism of the promised land in the works of Walter Brueggemann in comparison to his artistic source of influence, John Steinbeck. After the systematic analysis of Brueggemann’s criticism of land ideology throughout his work, I elaborate on Steinbeck’s critical attitude to this topic which I offer as Steinbeck’s own alternative criticism. On top of the affirmation that “Steinbeck may have put the issue of the land most eloquently,” as suggested by Brueggemann himself, I propose that Steinbeck (unlike Brueggemann) does not fall into the trap of producing an inverted ideology and offers a balanced and timeless criticism of the promised land issue.